The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3802/jgo.2024.35.e65
|View full text |Cite
|
Sign up to set email alerts
|

Evolving standards and future directions for systemic therapies in cervical cancer

Daniel Jia Ming Ang,
Jack Junjie Chan

Abstract: Several groundbreaking clinical trials with the potential to transform the management paradigm of both locally advanced and persistent, recurrent, or metastatic cervical cancers have been presented in 2023. This review describes the reported data from INTERLACE and KEYNOTE-A18 in the locally advanced setting, as well as BEATcc, innovaTV 301 and DESTINY-PanTumor02 for advanced disease. The practice implications of their positive results are interpreted in the context of global health considerations, and updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The incremental survival benefit in patients with stage IVB with the addition of IMT after applying propensity score analysis extends to prior retrospective studies [ 5 , 10 , 16 , 20 , 21 , 23 ] and is consistent with results from phase II and phase III clinical trials [ 23 , 24 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 44 , 45 ]. Outside of clinical trials, Perkins et al [ 25 ] reported a 24-month improvement in overall survival following CT + EBRT (whole pelvic radiation) vs. CT in a small multi-site retrospective cohort study with a median follow-up of 9 months.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The incremental survival benefit in patients with stage IVB with the addition of IMT after applying propensity score analysis extends to prior retrospective studies [ 5 , 10 , 16 , 20 , 21 , 23 ] and is consistent with results from phase II and phase III clinical trials [ 23 , 24 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 44 , 45 ]. Outside of clinical trials, Perkins et al [ 25 ] reported a 24-month improvement in overall survival following CT + EBRT (whole pelvic radiation) vs. CT in a small multi-site retrospective cohort study with a median follow-up of 9 months.…”
Section: Discussionsupporting
confidence: 80%
“…Our study included patients who were diagnosed through 2019 and found that patients who were treated with CT + EBRT + ICBT ± IMT had a 5-year survival rate between 40 and 55%. This doubling in 5-year survival likely reflects improvements associated with the use of intensity-modulated RT, stereotactic body RT, and high-dose ICBT [ 14 , 20 , 21 , 22 , 30 , 46 , 47 ] and the addition of bevacizumab, pembrolizumab, antibody drug conjugates, biologic response modifiers, and immune checkpoint inhibitors in the treatment of metastatic, recurrent, and persistent cervical cancer [ 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 48 ]. The study by Musa et al [ 39 ] showed that immunotherapy use has been increasing, but only a small subset of patients stayed on immunotherapy for prolonged periods, suggesting a need for more therapeutic options for first-line and second-plus-line treatments for metastatic, recurrent, or persistent cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that ICIs remain a viable option even after initial failure. Daniel Jia Ming Ang’s review [ 39 ] discusses ongoing clinical trials such as INTERLACE and KEYNOTE-A18, which are pivotal in shaping future treatment paradigms by integrating ICIs with other therapeutic modalities for both advanced and locally advanced cervical cancer. Further insights from Wutao Chen’s meta-analysis [ 40 ] indicate that in cervical cancer patients with low PD-L1 expression, ICI monotherapy was associated with adverse survival outcomes compared to ICI combination therapy or non-ICI treatments, with significant differences in OS (HR = 2.60) and PFS (HR = 7.59).…”
Section: Discussionmentioning
confidence: 99%